Wastewater Bio-solids Management for Fertilizer Quality Using Co- composting Process (Journal of Engineering, 2015)
Co-composting process can be acquired by combining organic fraction of municipal solid waste (OFMSW) with sewage sludge (SS) and mature compost (MC) as enhancement and bulking agent to overcome the problems of municipal solid waste and wastewater treatment plants besides the finally produced fertilizer usage for agriculture and horticulture. The effects of different mixture ratios of (OFMSW), (SS) and (MC) on the performance of composting process were investigated in this study. Piles of about 10 kg were prepared by mixing OFMSW, SS and MC in three different ratios (w/w) [OFMSW: SS: MC= 3:1:1, 3:2:1, and 3:3:1]. Results showed that the pile [3:1:1] was most beneficial to composting. The final compost products contained a C/N ratio (12.17), nitrification index (N-NH4/N-NO3) (0.2), organic matter degradation (36%), N content (1.75%), and Germintation Index (GI) 77.4%. Final compost showed low amounts of heavy metals, and significant reduction of pathogens indicating mature and stable bio-mass